Coexistence with Bears in Romania: A Local Community Perspective - Petru Tudor Stăncioiu; Ioan Dutcă; Marian Cristian Bălăcescu; Ștefan Vasile Ungurean (Sustainability, 2019)
In the modern context of the strict protection of large carnivores, the competition for resources between local community dwellers and these animals has become an important challenge for ensuring coexistence—the key for conservation success. To assess the perceptions of this intricate relationship, six local communities from Central Romania, located in areas with high-density brown bear (Ursus arctos L.) population and frequent conflicts, were investigated. A large proportion of the respondents (69%) showed various forms of intolerance (e.g., relocation, punishment, or killing) towards aggressive bears. However, the cognitive evaluation score derived from the level of interaction with bears showed a non-significant (p = 0.470) segregation by tolerance levels, suggesting that not only the tangible costs (direct damage) but rather the psychological costs of fear, danger, or risk are more important drivers of negative attitudes towards bears. Furthermore, the prevalent experienced emotions towards an inoffensive bear (fear, terror, and hate, which represent 73%) underline the general preference for living in “separate worlds”. This requires that bears should avoid humans and their settlements, a goal unlikely to be achieved under the current strict protection regime. Therefore, an alternative strategy that ensures mutual avoidance of the two players may be more appropriate for successful human–bear coexistence.